2011
DOI: 10.1097/won.0b013e3182152e93
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Certified Foot and Nail Care Nurses in the Prevention of Lower Extremity Amputation

Abstract: The primary purpose of this article is to outline the role, opportunities, and benefits of the certified foot and nail care nurse (CFCN). Current demographic trends toward an aging population and associated health issues such as diabetes mellitus, arthritis, peripheral arterial disease, dementia, and loss of visual acuity hinder self-care of the feet and nails. The resulting foot and nail care needs create opportunities for CFCN to promote health and prevent adverse outcomes such as infection and limb loss. Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…From the perspective of foot care nurses’ activities in routine foot and nail assessment, foot care, prevention of foot problems, and individualized patient education have been reported to be essential for achieving positive outcomes (Etnyre et al . , Aalaa et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of foot care nurses’ activities in routine foot and nail assessment, foot care, prevention of foot problems, and individualized patient education have been reported to be essential for achieving positive outcomes (Etnyre et al . , Aalaa et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-based practice in health care, including foot care, requires knowledge for the safe implementation of effective patient care (Melnyk & Fineout-Overholt 2010). From the perspective of foot care nurses' activities in routine foot and nail assessment, foot care, prevention of foot problems, and individualized patient education have been reported to be essential for achieving positive outcomes (Etnyre et al 2011, Aalaa et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…A basic foot exam—performed routinely and regularly on patients identified as having the potential of developing an ulcer. [ 8 , 9 , 10 , 11 ]. It is imperative that foot and nail care be delivered safely, effectively, and efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…It was determined whether the participant had received previous individual training on diabetic foot care and applications at least for two hours by examining the foot by diabetic training nurse and following-up according to the pre-defined risk group (8,9,20).…”
Section: Diabetic Foot Care and Training Formmentioning
confidence: 99%
“…It was reported in previous studies that half of the foot injuries are reported to be preventable with regular training and foot care. The easiest and cheapest way to prevent foot complications is to observe regularly, which is one of the most effective methods (8,9). Elderly with diabetes are in a highrisk group in terms of diabetic foot management (1).…”
Section: Introductionmentioning
confidence: 99%